Synthesis, Characterization and Modelling of Colloidal Quantum Dots - Karim, Md. Rezaul; Balaban, Mesut; Aydin, Hakan; Unlu, Hilmi; Yukselici, M. Hikmet (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Colloidal semiconductor nanocrystals with their diameters range between 2-10nmhave received great theoretical and experimental interest for both optical and electronical applications such as solar cells, light emitting diodes (LEDs), lasers and fluorescence imaging over the last few decades due to their size dependent optical, physical and chemical properties. In this chapter, we present a reviewabout the experimental and theoretical study about strain effects on core band gap and diameter of spherical bare CdSe core and CdSe/ZnS core/shell quantum dots (QDs) synthesized by using colloidal technique at varying temperatures. We will discuss the results of the structural, optical and dielectric characterizations. High resolution transmission electron microscopy (HRTEM) and x-ray diffraction (XRD) characterizations indicate that CdSe and CdSe/ZnS QDs have average particle sizes about 3.50 nm and 4.84 nm, respectively. Ultraviolet visible (UV-Vis) absorption and fluorescence emission spectroscopy measurements of first optical peak energies show that the compressive strain causes an increase (decrease) in the core band gap (diameter) of spherical CdSe/ZnS core/shell QDs at any temperature. Elastic strain modified effective mass approximation (EMA) predicts that there is a parabolic decrease (increase) in the core bandgap (diameter) of QDs with temperature. The diameter of spherical bare CdSe core and CdSe/ZnS core/shell QDs calculated by using strain modified EMA, with core bandgap extracted from absorption spectra are in excellent agreement with HRTEM data.
Keywords: II-VI; NANOCRYSTALS; DEPENDENCE; GROWTH; Science & Technology - Other Topics; Materials Science; Physics